1997
DOI: 10.1172/jci119171
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obese mice develop peripheral, but not central, resistance to leptin.

Abstract: Leptin administration reduces obesity in leptin-deficient ob/ob mice; its effects in obese humans, who have high circulating leptin levels, remain to be determined. This longitudinal study was designed to determine whether diet-induced obesity in mice produces resistance to peripheral and/or central leptin treatment. Obesity was induced in two strains of mice by exposure to a 45% fat diet. Serum leptin increased in proportion to body weight ( P Ͻ 0.00001). Whereas C57BL/6 mice initially responded to peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
451
6
10

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 698 publications
(509 citation statements)
references
References 26 publications
42
451
6
10
Order By: Relevance
“…21 Also, the serum leptin concentration rises in proportion to the amount of body fat in obese human subjects. 29,30 The notion of leptin resistance, a state of reduced responsiveness to leptin in various tissues, has recently come to be accepted, 31,32 and may explain why obesity causes immune dysregulation including tumor immunity. Although Dovio et al reported that the activity of NK cells did not differ between obese and nonobese humans, 33 it is not clear whether leptin resistance reflects the NK cell activity in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…21 Also, the serum leptin concentration rises in proportion to the amount of body fat in obese human subjects. 29,30 The notion of leptin resistance, a state of reduced responsiveness to leptin in various tissues, has recently come to be accepted, 31,32 and may explain why obesity causes immune dysregulation including tumor immunity. Although Dovio et al reported that the activity of NK cells did not differ between obese and nonobese humans, 33 it is not clear whether leptin resistance reflects the NK cell activity in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Diet-induced obesity in rodents is associated with elevated leptin levels [16] and such rats have apparent leptin resistance [3,4,17]. Identifying whether leptin resistance contributes to or is simply secondary to obesity is important in understanding the mechanisms underlying obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment by central rAAV-leptin delivery, which leads to both reduced signalling capacity and leptin resistance, exacerbates diet-induced obesity. Leptin resistance is the trademark of diet-induced obesity in rodents [3,4,17] and is generally considered a consequence rather than a cause of obesity. This simple view seems to be at odds with a recent study in transgenic mice overexpressing leptin [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although circulating leptin levels have not been measured in the present study, because of a lack of plasma, Trayhurn 44 suggested that such a lack of effect of exogenous leptin may be partly due to a suppression of endogenous leptin production. An alternative possibility is the development of resistance to peripherally, but not centrally, administered leptin in lean animals, 11,45 perhaps at the level of its transport into the brain. 46 For example, AKR lean mice fed a 10% fat diet were found to be sensitive to peripheral leptin until the day 56 of treatment, after which they were only sensitive to centrally administered leptin.…”
Section: Discussionmentioning
confidence: 99%